Utilization of virtual tours as a promotional strategy during the pandemic for Lembah Rembulan tourism - Dwi Intan Af'idah; Dairoh Dairoh; Ardi Susanto; Arief Rachman; Sharfina Febbi Handayani; Riszki Wijayatun Pratiwi (Community Empowerment, 2022)
Due to limited space for visitors and increasingly difficult promotional activities, the tourism sector is the sector most affected by the Covid-19 pandemic situation. This has a negative impact on visitor numbers. The Lembah Rembulan tourist attraction in Tegal Regency is one of the tours affected by Covid-19. As a result, a marketing strategy that can introduce tourism using existing technology other than social media, such as virtual tour applications, is required. The purpose of this community service is to create a virtual tour for the Lembah Rembulan tourist attraction and to assist the management team in using virtual tours as a pandemic tourism promotion strategy. This program uses socialization as a method, providing guidance on how to use applications, training on how to use virtual tour applications, and technical assistance of managing virtual tours. As a result, participants have a good understanding of how to use the Lembah Rembulan virtual tour. The fact that 91% of participants are familiar with the related virtual tour applications.